Determining and Strengthening Configurations of Instructional Leadership among Primary School Principals in Pakistan - Adeel Ahmed Khan (International Journal of Evaluation and Research in Education (IJERE), 2022)
The goal of this research is to add to the growing literature on educational leadership and management in Pakistan by coping with numerous objectives. To begin, the researchers wanted to see if an existing measurement tool, the Principal Instructional Management Rating Scale (PIMRS) Teacher Form, could be used in Pakistan. Second, this study aimed to explain instructional leadership configurations among a group of primary school principals in Pakistan. Third, the researchers looked into whether these major instructional leadership configurations were linked to student academic achievement. This study intended to expand the ‘indigenous knowledge base’ in Pakistan and furthermore adding to the expansion of the worldwide knowledge base. In this study, a quantitative survey method was applied. The sample included 440 teachers and 79 principals from 79 primary schools in Pakistan. Data collection employed PIMRS Teacher Form. In order to analyze the data, the researchers employed Cronbach's test of internal consistency, confirmatory factor analysis, and structural equation modelling.